Layanan informasi dalam mencegah negative peer pressure peserta didik - Rabiyah Al Adawiyah; Anna Rufaidah; Ajeng Radyati (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
the aim of the study was to determine the effect of information services in preventing negative peer pressure on students of SMK Bunda Kandung Jakarta. The research approach used by the author is quantitative with a survey method. The population of this study amounted to 226 students with an affordable population of 63 students and the sample in this study using a total sampling of 63 students. This study uses an instrument in the form of a questionnaire. The scale used is the Likert scale. Data were analyzed using simple linear regression test. The results showed that information services were able to prevent the occurrence of negative peer pressure on the students of SMK Bunda Kandung Jakarta